Sanitation resources for disabled individuals in Uganda - Harrison Schmachtenberger; Mei-Li Hey; Mikaya LD Lumori (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2022)
The material presented in this paper was derived from research on sources of current literature that address global sanitation problems, especially in Uganda. Information gathered from interviews with Ugandans provided a vital component. The paper presents background information on the sanitation issues faced by Ugandan children in general and by individuals with physical disabilities in particular. It reviews the global progress being made to achieve international goals of sanitation and hygiene and compares them to the situation in Uganda. In particular, the paper sheds light on how, in the past two decades, Uganda has made meaningful strides with regard to equal rights and societal inclusion for individuals with disabilities, including access to improved sanitation facilities as well as regulations to ensure the cleanliness and hygiene of public facilities. However, these achievements do not include assistive technologies that can enable the physically disabled to use the many sanitation resources such as pit latrines in rural areas. Finally, the paper describes research that focuses on a marginalized group of disabled Ugandans who are excluded from the solution landscape.